Determination of Knitted Fabric Porosity Using Digital Imaging Techniques. (26th October 2016) - Imrith, Manoj Kumar; Unmar, Roshan; Rosunee, Satyadev
Abstract : This paper has investigated the porosity of knitted fabrics using digital imaging techniques. A number of different methods have been proposed to determine the porosity of knitted fabrics, which include digital imaging, geometrical modeling, and air permeability. Digital imaging is an adequate technique to determine the porosity of high-porosity fabrics. In this work, eight types of knitted structures with eight different stitch lengths were produced on a flat-bed knitting machine. Porosity was determined using digital imaging techniques based on the method of threshold and pixel count, using a computer program developed for this work. The study consisted also of validating the results by including the data from two tested samples—from each set of knits throughout the use of regression equations which demonstrated that there is good correlation between the black mask and white mask images.